2020
DOI: 10.1002/ange.202001469
|View full text |Cite
|
Sign up to set email alerts
|

Openwork@Dendritic Mesoporous Silica Nanoparticles for Lactate Depletion and Tumor Microenvironment Regulation

Abstract: The direct depletion of lactate accumulated in the tumor microenvironment holds promise for cancer therapybut remains challenging.H erein, we report ao ne-pot synthesis of openwork@ dendritic mesoporous silica nanoparticles (ODMSNs) to address this problem. ODMSNs self-assembled through atime-resolved lamellar growth mechanism feature an openworked core and ad endritic shell, both constructed by silica nanosheets of % 3nm. With alarge pore size, high surface area and pore volume,O DMSNs exhibited ah igh loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…1i) was observed at 24 h. The tumor accumulation may bene t from the EPR effect of nanocomposites. Our previous experiment found that mice injected with free LOD died within 48 h. This phenomenon was also found by Tang [24]. The quick diffusion in blood and distribution in organs of free LOD may account for the phenomenon.…”
Section: Resultssupporting
confidence: 66%
“…1i) was observed at 24 h. The tumor accumulation may bene t from the EPR effect of nanocomposites. Our previous experiment found that mice injected with free LOD died within 48 h. This phenomenon was also found by Tang [24]. The quick diffusion in blood and distribution in organs of free LOD may account for the phenomenon.…”
Section: Resultssupporting
confidence: 66%
“…Enzyme-based nanomotors is one of the most typical chemical-fuel-driven nanomotors, which can generate a strong driving force to overcome random Brownian motion for efficient self-propulsion, relying on high efficient biocatalytic reactions of inherent biofuels in natural biological hosts. Owing to the highly specific enzyme-catalyzed reactions, the enzyme-based nanomotors show a very high selectivity to biofuels, which enables them to be driven only in specific physiological environment. Additionally, because the biological system can continuously generate the biofuel, the nanomotors are able to get a constant driving force for the long-lasting self-propulsion. Due to these unique properties and superior biocompatibility, a series of enzyme-based nanomotors have been developed, such as the urea-powered mesoporous silica nanoparticles (based on urease), glucose-powered stomatocyte-shaped polymer nanoparticles (based on glucose oxidase), the l -arginine-powered hyperbranched polymer nanospheres (based on NO synthase), triacetin mesoporous silica nanoparticles (based on lipase), etc. …”
Section: Introductionmentioning
confidence: 99%
“…(23)(24)(25). However, the composition of the obtained dendritic mesoporous nanoparticles is limited to SiO 2 , dopamine, resorcinol formaldehyde, Au, Pd, Pt, and Al 2 O 3 (26)(27)(28)(29)(30)(31)(32). The mesostructure of the reported porous rare earth-based materials is disordered, and its structural parameters are difficult to be regulated (33,34).…”
Section: Introductionmentioning
confidence: 99%